ANALISIS ORGANOLEPTIK MUTU HEDONIK DAN KIMIA BAKSO IKAN TUNA DENGAN PENAMBAHAN TEPUNG BUAH LINDUR (Bruguiera gymnorrhiza) - Lis Melissa Melissa Yapanto; Rahim Husain; Djainudin Djafar (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
This study aims to determine the use of lindur fruit flour (Bruguiera gymnorrhiza) in making tuna (Thunnus sp) meatballs. and knowing the characteristics of the organoleptic quality and chemical quality of tuna (Thunnus sp) meatballs with the addition of lindur fruit flour (Bruguiera gymnorrhiza). The treatment in this study was the addition of 20 gr, 30 gr and 40 gr lindur fruit flour to the tuna fish balls. The parameters tested were the organoleptic characteristics of hedonic quality which included appearance, aroma, taste and texture which were analyzed using Kruskall Walis. If the results obtained have a significant effect, then proceed with the Duncan test to see the differences in the formulation treatments tested. Chemical characteristics (protein, fat, moisture content, ash and carbohydrates) used a completely randomized design (CRD) and were analyzed by (ANOVA). The results of Duncan's continued test showed that the treatment of tuna meatball formulations with the addition of different lindur fruit flour produced organoleptic characteristics of hedonic quality, appearance, aroma, taste and texture were significantly different. ANOVA test results show that the chemical characteristics of tuna fish balls are protein content ranging from 12.13-15.18%, fat content from 3.73-4.52%, moisture content 15.04-16.55%, ash content 0.50. -0.55% and carbohydrates from 64.72 to 67.21%.